Vegetative propagation of acanthus: physiological-anatomical studies in regeneration - McMartin, Archibald (The University of Edinburgh, 1933)
The present work, while dealing with the origin of the regenerated organs, pursues the subject further and following the developmental anatomical features of these members subsequent to their initiation, shows how their internal construction is influenced in the first place by the internal organisation of the parent axis from which they arise, and secondly (in the case of roots) by the external environmental conditions in which they are produced. That the normal ontogenetic processes of an organ have/an influence on its regenerative phenomena is shown, especially in the case of leaf propagation, and in view of such a fact it has been found necessary to describe in some detail the differentiation of tissues occurring in the root and shoot as they pass from their embryonic condition to the attainment of maturity. These previously mentioned papers have shown how remarkably plastic this plant is when considered from the viewpoint of vegetative propagation; the present paper shows an equally remarkable plasticity in internal tissue organisation, and as the facts emerge it becomes very suggestive that the two sets of phenomena cannot be considered apart. Lastly, several points encountered during the investigation of leaf propagation suggested that an interesting comparison might be made between the anatomical changes occurring therein and the anatomy of the seedling. Accordingly, seedlings were raised, and as these exhibit some points of interest other than those for which they were originally intended, a fuller account of their development is given than was originally considered necessary.